Minimasi Waste Melalui Pendekatan Lean Manufacturing pada Proses Produksi di UMKM Nafa Cahya - Felia Ananda Cahya; Wiwik Handayani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
UMKM Nafa Cahya an individual business engaged in the industrial sector. The target of marketing is the lower class market with affordable prices. In production process, obstacles are found in the form of waste waiting and waste motion that must be trimmed or eliminated in order to achieve efficient production goals. By applying the lean manufacturing method it expected to be able to improve the current production process. The tools applied in this research are VSM, WAM which consists of WRM and WAQ, and fishbone. The results of study found that the most dominant is waste waiting by 22%, followed by an analysis fishbone and then a proposed improvement design for the production process was carried out.. Keywords: Waste, Lean Manufacturing, VSM, WAM, Fishbone